Enhanced-contrast optical readout in ultrafast broadband Raman quantum memories - Zheltikov, A. M. (Sci Rep, 2018)
The signal-to-noise contrast of the optical readout in broadband Raman quantum memories is analyzed as a function of the pulse widths and phase properties of tailored optical field waveforms used to write in and read out broadband photon wave packets. Based on this analysis, we quantify the tradeoff between the readout contrast and the speed of such memories. Off-resonance coherent four-wave mixing is shown to provide a source of noise photons, lowering the readout contrast in broadband Raman quantum memories. This noise cannot be suppressed by phase matching, but can be radically reduced with a suitable polarization arrangement and proper field-waveform tailoring.